Efficient isolation of human metapneumovirus using MNT‐1, a human malignant melanoma cell line with early and distinct cytopathic effects. (16th November 2017) - Sato, Ko; Watanabe, Oshi; Ohmiya, Suguru; Chiba, Fumiko; Suzuki, Akira; Okamoto, Michiko; Younghuang, Jiang; Hata, Akihiro; Nonaka, Hiroyuki; Kitaoka, Setsuko; Nagai, Yukio; Kawamura, Kazuhisa; et al.
ABSTRACT: Isolation of human metapneumovirus (HMPV) from clinical specimens is currently inefficient because of the lack of a cell culture system in which a distinct cytopathic effect (CPE) occurs. The cell lines LLC‐MK2, Vero and Vero E6 are used for isolation of HMPV; however, the CPE in these cell lines is subtle and usually requires a long observation period and sometimes blind passages. Thus, a cell line in which an early and distinct CPE occurs following HMPV inoculation is highly desired by clinical virology laboratories. In this study, it was demonstrated that, in the human malignant melanoma cell line MNT‐1, obvious syncytium formation occurs shortly after inoculation with HMPV‐positive clinical specimens. In addition, the growth and efficiency of isolation of HMPV were greater using MNT‐1 than using any other conventional cell line. Addition of this cell line to our routine viral isolation system for clinical specimens markedly enhanced isolation frequency, allowing isolation‐based surveillance. MNT‐1 has the potential to facilitate clinical and epidemiological studies of HMPV.